Fabrication of Organic Thin Film Transistor Arrays on Plastic and Paper Substrate for Flexible Display Application. Issue 1628 (18th March 2014) - Fujisaki, Y.; Nakajima, Y.; Nakata, M.; Tsuji, H.; Yamamoto, T.
ABSTRACT: Organic thin-film transistors (OTFTs) are the most promising candidates for flexible electronics owing to their flexible structures, the simplicity of processing large-area devices, and excellent compatibility with flexible substrates. To date, many studies have been reported that have aimed at developing a wide range of plastic electronics such as flexible displays, sensors. In this paper, we discuss our recent work, focusing on OTFT arrays and their application to flexible display. An active-matrix (AM) backplane using a low-temperature cross-linkable olefin-type polymer as the gatedielectric and an air-stable DNTT as the organic semiconductor (OSC) was successfully fabricated on a plastic substrate. The short-channel TFT array exhibited a high hole mobility of over 0.5 cm 2 /Vs, a low subthreshold slope of 0.31, and excellent environmental and operational stability. A 5-inch flexible OLED display exhibited a high luminescence of over 300 cd/m 2 by driving of the DNTT-based OTFTs. Solution-processed OTFTs are also attracting considerable attention owing to both their simple manufacturing process and excellent transistor performance. We present a simple patterning process for a solution-processable OSC that can be used to develop a high-mobility short-channel TFT array. The OSC film was directly patterned on the confined active channel region by a simple lamination coating technique and the resulting TFTs showed a high mobility of up to 1.3 cm 2 /Vs. In the final section, we report on eco-friendly paper-based organic TFT array. A transparent cellulose nanofibers paper was firstly applied to a flexible substrate for the TFT backplane. A solution-processed TFT on the transparent paper exhibited a high mobility exceeding 1 cm 2 /Vs, good air stability, and excellent mechanical stability.